FAKTOR PENDORONG DAN FAKTOR PENGHAMBAT PARTISIPASI MASYARAKAT DALAM PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN REJOMULYO KECAMATAN SEMARANG TIMUR KOTA SEMARANG - Ayu Wastiti; Hartuti Purnaweni; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
The Directorate General of Human Settlements, Ministry of Public Works and Public Housing, initiated the construction of a collaboration platform through the City Without Slums Program (KOTAKU), thus every government policy in an effort to empower the community. Community participation is very important in achieving success and sustainability and is one of the benchmarks for the success of the Kotaku Program. This paper was written to explore more about the driving and inhibiting factors of community participation. The research method used based on the above understanding is using a qualitative descriptive type method. The purpose of this study was to analyze the driving factors and inhibiting factors of community participation in the Kotaku Program in Rejomulyo Village, East Semarang District. The people in Rejomulyo have a high willingness to participate in the Community Kotaku Program to take part in planning through representatives and attend socialization organized and take care of the results of development. Meanwhile, the main factor that hinders community participation is the economic condition which includes work and income, which is a factor inhibiting community participation, because people have to work for money so they do not have time to participate in the implementation and only participate in their spare time. The community is also unable to contribute funds to the Kotaku Program due to low incomes. The recommendation for this research is that a schedule for the implementation of work for residents in the afternoon or evening should be made and a village development savings or savings system made from the community, whose money is withdrawn routinely every day with a small nominal that is mutually agreed upon.